EXPLANATORY ANALYSIS OF FINANCIAL PLANNING ON HOUSEHOLD FINANCIAL BEHAVIOR - Andoko, Andoko; Martok, Yenni (Universitas Pelita Harapan Medan, 2020)
The purpose of this study is to analyse financial planning on the financial behaviour of household. Research method is using library research. From the discussion, it can be concluded that financial planning is the tool for the financial decision making for family. Financial planning is the process where someone can fulfil the requirement of daily life. It will be done by doing or implementing according to the planning process that he understand. Financial planning is very important to make sure that the life will be better for the people. Household financial behaviour is important to wealth building. Ignorance of financial concepts involves great uncertainty about the future. Financial planning has positive effects to financial behaviour of household entities. Financially secure families are able to contribute and foster community economic development.Keywords: Financial Planning, Household Financial Behaviour AbstrakPenelitian bertujuan untuk menganalisa perencanaan keuangan pada perilaku keuangan rumah tangga. Metode penelitian menggunaka penelitian kepustakaan. Dari pembahasan penelitian ini, dapat disimpulkan bahwa perencanaan keuangan dapat disimpulkan bahwa literasi keuangan dan perencanaan keuangan dapat disimpulkan bahwa literasi keuangan dan perencenaan keuangan adalah alat untuk membuat keputusan keuangan di keluarga. Perencanaan keuangan adalah suatu proses dimana seseorang dapat memenuhi kebutuhan dari kehidupan sehari hari. Itu akan dilakukan dengan pengerjaan atau implemntasi dari proses perencanaan yang dia mengerti. Perencanaan keuangan sangatlah penting untuk memperhatikan hidup seseorang menjadi baik untuk orang lain. .Perilaku keuangan rumah tangga penting untuk pembangunan kekayaan. Ketidaktahuan pada konsep keuangan melibatkan ketidakpastian yang besar di masa depan. Perencanaan keuangan mempunyai efek yang positif ke perilaku keuangan rumah tangga. Keluarga yang aman secara keuangan dapat memberikan kontribusi dan mendorong pembangunan ekonomi dalam komunitas. Keywords: Perencanaan Keuangan, Perilaku Keuangan Rumah Tangga